Given the following two propositional forms, prove whether or not they are logically equivalent.

$(a \wedge \neg c) \vee (b \wedge c)$

$(a \wedge \neg c) \vee (b \wedge c) \vee (a \wedge b)$

I've written out a truth table for both expressions, and I can see that they are in fact logically equivalent; however, I was wondering how to go about approaching this problem more elegantly using rules of equivalence as opposed to a brute force truth table solution. Thank you!

  • 1
    $\begingroup$ The consensus theorem. $\endgroup$ – Fabio Somenzi Feb 5 '18 at 19:09
  • $\begingroup$ That clarified things nicely thank you. $\endgroup$ – rcmpgrc Feb 6 '18 at 1:21

You can do:

$$(a \land \neg c) \lor (b \land c) \lor (a \land b) \overset{Adjacency}{\Leftrightarrow}$$

$$(a \land \neg c) \lor (b \land c) \lor (a \land b \land c) \lor (a \land b \land \neg c)\overset{Absorption \times 2}{\Leftrightarrow}$$

$$(a \land \neg c) \lor (b \land c)$$

| cite | improve this answer | |

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.